Spatial Dynamics and Regional Spillover Effects of Manufacturing GDP Growth in Indonesia - Abdul Azis; Etty Soesilowati; Thomas Sosecco; Inayati Nuraini Dwiputri; Farida Rahmawati; Hasan Adi Nugraha (Pusbindiklatren Bappenas, 2026)
This study examines the spatial dynamics and regional spillover effects of manufacturing GDP growth across provinces in Indonesia during the period 2019–2023. Regional disparities and uneven industrial development remain critical challenges in achieving inclusive and sustainable economic growth, particularly in the context of spatial inequality and structural transformation. Using an Exploratory Spatial Data Analysis (ESDA) approach, including Global Moran’s I, LISA Cluster Map, and spatial visualization, this study identifies patterns of spatial dependence and regional clustering. The results reveal consistent positive spatial autocorrelation, indicating that manufacturing growth is spatially interdependent rather than randomly distributed. The analysis identifies three phases of spatial dynamics: pre-disruption integration, spatial decoupling during economic shocks, and post-pandemic re-convergence. A High–High cluster in Sulawesi indicates the emergence of a new growth pole driven by agglomeration forces and spatial spillover effects, while persistent Low–Low clusters in Papua reflect the presence of spatial low-growth traps. These findings highlight the importance of spatially integrated industrial policies, strengthening interregional connectivity, and addressing structural disparities to support more inclusive and sustainable development. This study contributes to the achievement of SDG 8 and SDG by providing empirical evidence on spatial inequality and regional growth dynamics in Indonesia.